Bioactive compounds, antioxidant activity, and mineral content of bróquil: A traditional crop of Brassica oleracea var. italica - Montaner, Celia; Mallor, Cristina; Laguna, Sonia; Zufiaurre, Raquel (Frontiers in Nutrition, 2023)
Brassicaceae edible plants are rich in bioactive compounds and promote health benefits. However, there is less interest in expanding knowledge about the Brassica cultivars to date. In particular, underutilized species and local cultivars could constitute a source of agrodiversity in adapting to the territory with likely higher contents of nutraceutical compounds. In this context, Bróquil (Brassica oleracea var. italica) is a traditional Brassicaceae crop grown in the Spanish region of Aragón. Currently, it is cultivated mainly in family orchards for autoconsumption and, in minority, in small farms for local markets. This study evaluates a collection of 13 bróquil landraces from the Spanish Vegetable Genebank of the Agrifood Research and Technology Center of Zaragoza (BGHZ-CITA), describing their mineral contents, bioactive compounds, and antioxidant activities, including a broccoli commercial variety “Parthenon” as the control. The study reports data on the health-promoting nutrients and antioxidants of bróquil for the first time. Under our experimental conditions, we found that bróquil has a great variability for these compounds that showed on average similar or higher levels than the broccoli control. The different bróquil landraces also revealed variability in both intraccessions and interaccessions due to the lack of a formal breeding selection. Despite this variability, we highlight accession HB5 that corresponds to Headed Bróquil BGHZ6685. In particular, we can stand out its antioxidant activity of 87.07 ± 0.81%I, total phenolic content of 13.21 ± 0.53 mg GAE g−1 dw, total flavonoid content of 14.50 ± 1.29 mg QE g−1 dw, total glucosinolate content of 43.70 ± 1.09 mg SnE g−1 dw, and vitamin C content of 7.21 ± 0.13 mg AA g−1 dw. Regarding bróquil mineral composition, K was the highest macroelement (22.66–33.62 mg g−1 dw), followed by Ca, P, and S whose values were relatively lower compared to K. Mg and Na showed the lowest values. Among the microelements evaluated (Mn, Zn, and Fe), iron was the most abundant detected, higher in all bróquil accessions than in broccoli, except for one accession. Therefore, the results reported for bróquil landraces show promising nutritional quality. This could lead to an increase in agrobiodiversity and contribute to a more diversified and healthy diet.